2010
DOI: 10.1051/0004-6361/201014797
|View full text |Cite
|
Sign up to set email alerts
|

The stellar content of the Hamburg/ESO survey

Abstract: We determine the metallicity distribution function (MDF) of the Galactic halo based on metal-poor main-sequence turnoff-stars (MSTO) which were selected from the Hamburg/ESO objective-prism survey (HES) database. Corresponding follow-up moderateresolution observations (R 2000) of 682 stars (among which 617 were accepted program stars) were carried out with the 2.3 m telescope at the Siding Spring Observatory (SSO). Corrections for the survey volume covered by the sample stars were quantitatively estimated and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
40
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 64 publications
(59 reference statements)
6
40
0
Order By: Relevance
“…Early surveys for the most metal-poor stars in the halo (see below) indicated that the number of stars smoothly declined with metallicity (a factor of 10 in decline for every 1 dex in [Fe/H]) down to at least [Fe/H]∼ −3.5. Lower than this, some samples indicated a sharp cut-off at [Fe/H] = −3.6, with very few stars more metal-poor than this value (Schörck et al 2009;Li et al 2010). However, this cut-off is not seen in other samples (Yong et al 2013b).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Early surveys for the most metal-poor stars in the halo (see below) indicated that the number of stars smoothly declined with metallicity (a factor of 10 in decline for every 1 dex in [Fe/H]) down to at least [Fe/H]∼ −3.5. Lower than this, some samples indicated a sharp cut-off at [Fe/H] = −3.6, with very few stars more metal-poor than this value (Schörck et al 2009;Li et al 2010). However, this cut-off is not seen in other samples (Yong et al 2013b).…”
Section: Introductionmentioning
confidence: 85%
“…These surveys exploited the stars' tendency to have large proper motions (e.g., Ryan & Norris 1991;Carney et al 1996) or the wide-field capabilities of Schmidt telescopes. Objective prism observations of millions of stars, carried out by such landmark surveys as the HK Survey (Beers et al 1992) and the Hamburg-ESO Survey (Christlieb et al 2008) on Schmidt telescopes led to the medium-resolution spectroscopic followup of thousands of EMP star candidates (Norris et al 1999;Frebel et al 2006;Schörck et al 2009;Li et al 2010;Placco et al 2011). Of these, of order several hundred have been followed up with high-resolution spectroscopy and detailed element abundance analyses (e.g., McWilliam et al 1995;Norris et al 1996Norris et al , 2013Ryan et al 1996;Aoki et al 2002;François et al 2003;Cayrel et al 2004;Cohen et al 2004Cohen et al , 2013Lai et al 2008;Hollek et al 2011;Placco et al 2014a;Roederer et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Schörck et al (2009) and Li et al (2010) published metallicities for HES stars based on medium-resolution spectra. For our combined sample (program stars and literature stars), there are 12 stars in common with Schörck et al (2009) and Li et al (2010). Recall that there are program stars for which we conducted analyses assuming a dwarf gravity and a subgiant gravity.…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…The addition of Schörck et al 2009;Li et al 2010) may be due to selection biases. Indeed, the recent work of Yong et al (2013b) presents 10 new stars with [Fe/H] < −3.5, and the tail of the low-metallicity MDF when these data are included exhibits a smooth decrease down to [Fe/H] = −4.1.…”
Section: Comparison With Other Studies and Interpretationsmentioning
confidence: 99%